Morphological similarities between Amphisbaena mitchelli Procter, 1923 and A. miringoera Vanzolini, 1971 (Squamata: Amphisbaenidae): phylogenetic relatedness or morphological convergence? - Almeida, João Paulo Felix Augusto De; Vechio, Francisco Dal; Teixeira, Mauro Jr.; Rodrigues, Miguel Trefaut; Mott, Tamí (Zootaxa, 2016)
To date, 22 species of amphisbaenids have been recorded at Brazilian Amazon (Ribeiro et al. 2008), six of them are small and have two pre-cloacal pores (Hoogmoed & Ávila-Pires 1991; Teixeira Jr. et al. 2014). Most of these species have narrow distributions, and its biology and phylogenetic relationships are poorly understood (Hoogmoed & Ávila-Pires 1991). Amphisbaena mitchelli Procter, 1923 and A. miringoera Vanzolini, 1971 share several morphological similarities that could reflect phylogenetic relatedness (Vanzolini 1971). Both have two pre-cloacal pores and a similar pattern of head scutelation, but whereas the first has 193–220 and 26–29 body and tail annuli, respectively, the latter has 250–264 and 22–24 (Vanzolini 1971).